Microcapsule of Sweet Orange Essential Oil Encapsulated in Beta‐Cyclodextrin Improves the Release Behaviors In Vitro and In Vivo. Issue 9 (29th July 2018) - Li, Dahu; Wu, Houjiu; Huang, Wei; Guo, Li; Dou, Huating
Abstract : To protect sweet orange essential oil (SOEO) from volatilization and oxidation, and also to expand the range of application in physiology or medicine, beta‐cyclodextrin (β‐CD) is employed to develop SOEO microcapsules via an inclusion encapsulation method in this study. An optimal encapsulating condition obtained from response surface methodology (RSM) is an SOEO mass of 5.66 g, an encapsulating time of 3.24 h, and an encapsulating temperature of 53.7 °C, which provides the greatest encapsulation efficiency (EE) of 50.31%. Particle size and scanning electron microscope (SEM) reveal that rhombus, trapezoid, and parallelogram can be found in optimized microcapsule aggregates with a particle size of 1.34 ± 0.58 µm. Fourier transform infrared spectroscopy (FT‐IR) and differential scanning calorimetry (DSC) confirm the encapsulation of SOEO in β‐CD. Furthermore, the release study in vitro suggests that SOEO in microcapsules can be better released in simulated gastric fluid (SGF) than in simulated intestinal fluid, and the study in vivo suggests that, β‐CD might increase the solubility and bioavailability of SOEO. Thus, the microcapsules have potentials to be applied to the biomedical industry. Practical Applications : The optimal encapsulating condition is attained using RSM, and SOEO is capsuled to be a stable form in optimized microcapsules. The active ingredients of SOEO can be exerted fully by microcapsules. The microcapsules have excellent potentials for use as biological or pharmaceutical products. In this study, microcapsules of SOEO are developed using RSM. The physical and chemical characterizations of SOEO microcapsules are analyzed. The release behaviors in vitro and in vivo are also researched. Though these works, the microcapsules increase the solubility and bioavailability of SOEO, which has potentials for application in the biomedical industry. Abstract : In this study, microcapsules of SOEO are developed using RSM. The physical and chemical characterizations of SOEO microcapsules are analyzed. The release behaviors in vitro and in vivo are also researched. Though these works, the microcapsules increase the solubility and bioavailability of SOEO, which has potentials for application in the biomedical industry.